Multi-strain probiotics attenuate carbohydrate-lipid metabolic dysregulation in type 2 diabetic rats via gut-liver axis modulation - Yecheng Gao; Yanfang Liu; Zelong Li; Liyi Lu; Yajuan Guo; Dun Su; Heping Zhang (mSystems)
ABSTRACT Type 2 diabetes mellitus (T2DM) is a pervasive chronic metabolic disorder characterized by dysregulation of carbohydrate, protein, and lipid metabolism. The objective of this study was to elucidate the impact of multi-strain probiotic supplementation on the metabolism of carbohydrates and lipids and the interplay between the gut and liver in a T2DM rat model. A total of 32 rats were randomly assigned to four experimental groups: a control group, a T2DM model group, a low-dose probiotics group, and a high-dose probiotics group. The impact of probiotic intervention on glycemic and lipid profiles was evaluated, with a specific emphasis on the high-dose cohort. The treatment with multi-strain probiotics, consisting of three Lacticaseibacillus species and one Bifidobacterium species, resulted in a significant improvement in blood glucose and lipid profiles in T2DM rats, with the highest dosage demonstrating the most pronounced effects. Probiotic administration modulated gut microbiota composition and diversity, enriching potentially beneficial bacterial species and altering gut metabolic modules and carbohydrate-active enzyme profiles. Multi-omics analyses indicated that alterations in fecal short-chain fatty acids and serum bile acids may serve as pivotal mediators for crosstalk between hepatic and gut transcriptomic pathways. This study offers novel insights into the role of probiotics in managing T2DM via the gut-liver axis, emphasizing the potential of probiotic therapy in modulating key metabolic pathways.IMPORTANCEType 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia, caused by defects in insulin secretion, insulin action, or both. For individuals diagnosed with T2DM, managing diabetes-related complications is often the most challenging aspect. Exogenous probiotics have the potential to serve as a promising therapeutic strategy to improve diabetes-related symptoms. We conducted a 64-day animal experiment to investigate the effects of probiotics on T2DM-related metabolic disorders and dyslipidemia by feeding four mixed probiotics to T2DM rats. The results showed that probiotics exerted beneficial effects on glucose- and lipid-related homeostasis indices in diabetic rats to some extent and modulated the gut microbiota to manage T2DM via the gut-liver axis.